Inner SPACE: 400-Micron Isotropic Resolution MRI of the Human Brain - Shepherd, Timothy M.; Hoch, Michael J.; Bruno, Mary; Faustin, Arline; Papaioannou, Antonios; Jones, Stephen E.; Devinsky, Orrin; Wisniewski, Thomas (Frontiers in Neuroanatomy, 2020)
Objectives: Clinically relevant neuroanatomy is challenging to teach, learn and remember since many functionally important structures are visualized best using histology stains from serial 2D planar sections of the brain. In clinical patients, the locations of specific structures then must be inferred from spatial position and surface anatomy. A 3D MRI dataset of neuroanatomy has several advantages including simultaneous multi-planar visualization in the same brain, direct end-user manipulation of the data and image contrast identical to clinical MRI. We created 3D MRI datasets of the postmortem brain with high spatial and contrast resolution for simultaneous multi-planar visualization of complex neuroanatomy. Materials and Methods: Whole human brains (N=5) were immersion-fixed in 4% formaldehyde for 4 weeks, then washed continuously in water for 48 hrs. The brains were imaged on a clinical 3-T MRI scanner with a 64-channel head and neck coil using a 3D turbo spin echo sequence with 400-micron isotropic resolution (voxel = 0.064 mm3; time = 7 hrs). Besides resolution, this sequence has multiple adjustments to improve contrast compared to a clinical protocol, including 93% reduced turbo factor and 77% reduced effective echo time. Results: This MRI microscopy protocol provided excellent contrast resolution of small nuclei and internal myelinated pathways within the basal ganglia, thalamus, brainstem and cerebellum. Contrast was sufficient to visualize the presence and variation of horizontal layers in the cerebral cortex. 3D isotropic resolution datasets facilitated simultaneous multi-planar visualization and efficient production of specific tailored oblique image orientations to improve understanding of complex subcortical anatomy. Conclusions: We created an unlabeled high-resolution digital 3D MRI dataset of neuroanatomy as an online resource for readers to download, manipulate, annotate and use for clinical practice, research and teaching that is complementary to traditional histology-based atlases. Digital MRI contrast is quantifiable, reproducible across brains and could help validate novel MRI strategies for in vivo structure visualization.